Effect of spraying levels of nano fertilizer (NPK) and biochar on the growth and yield of wheat - Mazen Awad Kazem; Rahim Alwan Haloul (University of Thi-Qar Journal of agricultural research, 2024)
The study was carried out at the second research station of the College of Agriculture, Al-Muthanna University. The purpose was to investigate the impact of different amounts of nano-NPK fertilizer and biochar on the availability and concentration of NPK in wheat plants, as well as their growth and yield. The experiment was conducted using a mixed soil. The experiment involved the application of five different concentrations of nano-NPK fertilizer, which were labeled as follows: (A0) Control treatment,(A1) Full recommendation of traditional agrarian NPK, (A2) 2/1 recommendation of traditional agrarian NPK + 2/1 recommendation of nano-NPK, (A3) Full recommendation of nano-NPK + 2/1 recommendation of traditional agrarian NPK, (A4) Double recommendation of nano-NPK + 2/1 recommendation of traditional agrarian NPK. There are four levels of biochar represented by the symbols (B0:0%), (B1:1%), (B2: 2%), and (B3: 3%). The addition was based on the measurement of the volume of dry soil. A factorial experiment was conducted using a randomized complete block design (RCBD) with three repetitions. The averages were compared using the least significant difference (L.S.D) test. With a significance threshold of 0.05. The findings demonstrated substantial variations in the effects of incorporating different amounts of spraying with nano-NPK fertilizer and biochar, as well as their interaction, on plant height, flag leaf area, chlorophyll index, number of tillers, thousand grain weight, and grain yield.